Real-world data on aortic endografts: Gore Together aortic registry protocol - Dai Yamanouchi; Manar Khashram; Dennis Gable; Ross Milner; Kak Khee Yeung; Timothy A. Resch; Dittmar Böckler; Chris Delaney; Ali Azizzadeh; Kazuo Shimamura; Raffi Qasabian; Sukgu Han; et al. (Frontiers in Cardiovascular Medicine, 2026)
Background Post-market long-term surveillance data for aortic endovascular devices are essential due to evolving regulatory standards and clinical practice demands. Building upon the successful Global Registry for Endovascular Aortic Treatment (GREAT), comprehensive real-world data is required to address current gaps in long-term device performance and patient outcomes. Thus, the purpose of this manuscript is to describe the protocol, objectives, and anticipated outcomes of the Gore Together Aortic Registry, designed for extensive real-world evaluation of the performance and clinical outcomes of aortic endovascular devices. Methods The Gore Together Aortic Registry is an international, prospective, observational registry initiated in response to increased regulatory emphasis on long-term post-market surveillance. This registry will enroll approximately 3,355 adult patients (≥18 years old) from over 170 global clinical centers, undergoing routine clinical care with GORE® aortic endovascular devices. Enrollment commenced based on standard clinical application, with data and imaging collection beginning at the time of hospitalization, and at each follow-up period. Ethics and dissemination Primary registry outcomes include technical deployment success, measures of device or procedural adverse events, including endoleaks, as well as post-procedure reinterventions. Individual modules can tailor their reporting to address pertinent needs that may include dissection characterization, neurological complications or renal dysfunction. Follow-up is collected per standard of care with the potential to capture up to 10 years of data based upon device need. Patient enrollment is ongoing; no results are reported at this stage. Conclusion The Gore Together Aortic Registry aims to deliver robust and granular real-world data regarding mid-term clinical outcomes of aortic endovascular devices, enhancing patient care strategies and meeting evolving global regulatory expectations. Results will guide clinical decisions, inform regulatory oversight, and potentially improve device safety and efficacy. Clinical trial registration The individual modules of the Gore Together Aortic Registry are registered in ClinicalTrials.gov as: https://clinicaltrials.gov/study/NCT06218875 , identifier NCT06218875 https://clinicaltrials.gov/study/NCT06507865 , identifier NCT06507865 https://clinicaltrials.gov/study/NCT06658730 , identifier NCT06658730